Polar Intermetallics Pr5Co2Ge3 and Pr7Co2Ge4 with Planar Hydrocarbon‐Like Metal Clusters. Issue 44 (18th July 2017) - Lin, Qisheng; Aguirre, Kaiser; Saunders, Scott M.; Hackett, Timothy A.; Liu, Yong; Taufour, Valentin; Paudyal, Durga; Budko, Sergey; Canfield, Paul C.; Miller, Gordon J.
Abstract: Planar hydrocarbon‐like metal clusters may foster new insights linking organic molecules with conjugated π–π bonding interactions and inorganic structures in terms of their bonding characteristics. However, such clusters are uncommon in polar intermetallics. Herein, we report two polar intermetallic phases, Pr5 Co2 Ge3 and Pr7 Co2 Ge4, both of which feature such planar metal clusters, namely, ethylene‐like [Co2 Ge4 ] clusters plus the concatenated forms and polyacene‐like [Co2 Ge2 ] n ribbons in Pr5 Co2 Ge3, and 1, 2, 4, 5‐tetramethylbenzene‐like [Co4 Ge6 ] cluster in Pr7 Co2 Ge4 . Just as in the related planar organic structures, these metal–metalloid species are dominated by covalent bonding interactions. Both compounds magnetically order at low temperature with net ferromagnetic components: Pr5 Co2 Ge3 through a series of transitions below 150 K and Pr7 Co2 Ge4 through a single ferromagnetic transition at 19 K. Spin‐polarized electronic structure calculations for Pr7 Co2 Ge4 reveal strong spin‐orbit coupling within Pr and considerable magnetic contributions from Co atoms. This work suggests that similar structural chemistry can emerge for other rare‐earth/late‐transition‐metal/main‐group systems. Abstract : Polyatomic and valence‐electron‐rich Co–Ge clusters with planar hydrocarbon‐like geometries are identified in Pr5 Co2 Ge3 and Pr7 Co2 Ge4 (see scheme). Complex magnetic properties arise from interactions between Pr and these Co–Ge species.